The Role of Artificial Intelligence as a Strategic Tool for Effective Execution of Total Quality Management Practices in an Institutional Management - Madiha; Naqvi, Syeda Amina Batool; Fatima, Urooj; Ishaque, Samyyia (ACADEMIA International Journal for Social Sciences, 2026)
This paper discusses how to incorporate the use of the artificial intelligence (AI) tools in the promotion of Total Quality Management (TQM) within the learning institutions. With the trend of digital transformation as educational institutions embrace the notion, AI tools are finding their way into facilitating the administrative process, enhancing decision-making, and improving student outcomes. The main aim of the study was to investigate the role played by AI tools in enhancing institutional management, decision-making, and academic success. Survey was conducted on a variety of public and private institutions in Pakistan, assessing their use of AI tools including predictive analytics, machine learning algorithms, natural language processing (NLP) and automated administrative systems. The results show that AI tools have a significant positive impact on TQM, especially regarding the aspects of optimizing processes, improving operational efficiency, and retention of students. The application of AI-powered systems, in particular, predictive analytics, was found to have a positive influence on the institutional performance: It helps to improve decisions and identify the student at risk early enough, allowing making early interventions. Moreover, AI-driven automation in the administrative process, including grading and scheduling, led to a decrease in workload, and a more efficient distribution of resources. Nevertheless, opposition to change, data privacy, and infrastructural constraints are other challenges to AI uptake in some institutions highlighted in the study. The study finds that although AI has significant potential in enhancing TQM practices in educational institutions, attaining success requires the commitment of a leadership team, proper investment in the appropriate infrastructure, and implementation of comprehensive training programs. In addition, an establishment of ethical principles of using AI, especially in terms of data privacy, algorithmic fairness, and so on, is a key to building trust and ensuring the responsible adoption of AI. Future research and practical use recommendations are given with a focus on the importance of further exploration of AI and its long-term influence on the practices of TQM and the overall standard of education.